Effect of adding sunflower oil in the ration on some productive traits in Awassi ewes - AL-Mosawi, Jassim E. (The Iraqi Journal of Veterinary Medicine, 2015)
This study was designed to investigate the effects of the addition of different ratios of sunflower oil to the diet of Awasi ewes on the rumen fermentation and milk composition. It was conducted by using 12 Awassi ewes (2-3.5 years old) with average body weight 56.62 kg. The ewes were randomly divided into three groups. Each group had four ewes according to the age, body weight and milk yield. The ewe in each group received 1.4 kg/ dry matter for three rations consisting of barley, wheat bran, soybean meal and alfalfa hay. The first group was fed on control ration, while 2.5 and 5 % of sunflower oil were included in the rations of the second and third groups, respectively. The results showed that the treatments had no significant effect on the average body weight, milk production and milk composition (lactose, protein and SNF percentage). Milk Fat percentage was significantly (P<0.05) decreased in second and third groups (4.30 ±0.31 and 4.23 ±0.40) %, respectively as compared with the control group (5.89 ±0.53 %). The pH value of rumen liquor in hours (0 and 3) after feeding showed no significant differences between groups, also there were no significant differences in the volatile fatty acid and ammonia concentration in the rumen liquor in all groups, despite that the volatile fatty acid decreased insignificantly in all treated groups as compared with the control group after feeding. The blood parameters were not affected by the experimental treatments. These results indicated that the fermentation patterns were affected by the increased oil supplementation to the diet of ewes.